Implementasi Teori al-Maslahah Najmuddin ath-Thufi dalam Fatwa Politik Yusuf al Qaradhawi - Habibi, Mohamad Ramadan; Nurjanah, Siti; Zulaikha, Siti; Hermanto, Agus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Politics is a dynamic topic that follows the development and needs of the times. This reality needs to be taken seriously by researchers to determine dhowabhit syar’I so that political activities do not go off track. Najmuddin ath Thufi is one of the scholars who emphasizes the flexible and responsive nature to changes in social and political conditions. This principle is oriented towards the common good, and its relevance is apparent in answering various contemporary issues including the theme of Islamic Politics. This study uses a qualitative analysis method. The data that the author has analyzed shows that the theory of al Maslahah ath Thufi is widely used by Yusuf al Qaradhawi in contemporary political fatwas.